An electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material and its preparation method and application

By electrostatic self-assembly of SnO2@NDPC/MXene nanocomposite, the problems of energy storage kinetic mismatch and poor cycle stability of the lithium-ion capacitor negative electrode material are solved, and high specific capacity and excellent rate performance are achieved.

CN114613952BActive Publication Date: 2025-03-11SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210182418.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-25
Publication Date
2025-03-11
Estimated Expiration
2042-02-25

AI Technical Summary

Technical Problem

The existing lithium-ion capacitor negative electrode materials have problems such as energy storage kinetic mismatch, low capacity, poor rate performance and poor cycle stability, which limits their application.

Method used

SnO2@NDPC/MXene nanocomposites were prepared by electrostatic self-assembly method, and nanosized SnO2 particles were filled with a multi-stage porous structure of nitrogen-doped porous carbon, and the SnO2@NDPC substrate was tightly wrapped by a single layer of MXene nanosheets to avoid the synthesis conditions of high temperature, water and oxygen content, and improve the specific capacity and cycle stability of the material.

Benefits of technology

It achieves high specific capacity, excellent rate performance and good cycle stability, and is suitable for negative electrode materials for lithium-ion batteries and lithium-ion capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114613952B_ABST
    Figure CN114613952B_ABST
Patent Text Reader

Abstract

The present invention discloses an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material, and a preparation method and application thereof. The method comprises: using a deep low eutectic solvent to prepare nitrogen-doped porous carbon (NDPC), dripping a SnCl2 solution into its acetone dispersion, and calcining to obtain a composite material (SnO2@NDPC) embedded with ultrafine SnO2 nanoparticles. The prepared MXene and SnO2@NDPC with opposite charges are electrostatically self-assembled in an aqueous solution and freeze-dried to obtain a SnO2@NDPC / MXene nanocomposite material. The method avoids the unfavorable conditions of easy oxidation during the preparation of the MXene composite material, and the obtained nanocomposite material has a highly conductive multi-level structure, which promotes electron transport and Li + The migration of SnO2 and the volume expansion during the charge and discharge process are alleviated. This material has a good application prospect as a negative electrode material for lithium ion capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation and application of negative electrode materials for lithium ion capacitors (LICs), and specifically relates to an electrostatic self-assembled SnO2@NDPC / MXene nanocomposite material and a preparation method and application thereof. Background Art

[0002] With the increasing prominence of energy shortage and environmental governance issues, seeking a high-performance, long-cycle-life energy storage system has become the main research direction. Compared with traditional lithium-ion secondary batteries, lithium-ion capacitors have relatively large energy density and power density, showing their unique advantages. However, due to the unique structure of lithium-ion capacitors, the mismatch between the energy storage kinetics of the battery-type negative electrode and the capacitor-type positive electrode leads to low capacity and poor rate performance, which limits their application. Therefore, it is of great significance to develop an ideal lithium-ion capacitor negative electrode material with high specific capacity, fast lithium ion insertion / deinsertion mechanism, and good cycle stability.

[0003] MXene (Ti3C2) is an emerging two-dimensional transition metal carbide material, which is generally obtained by etching its ternary ceramic precursor MAX phase material (Ti3AlC2). In actual operation, the A (Al) layer is selectively etched by an etching solution containing fluorine ions to obtain an organ-shaped multilayer MXene material, which is then followed by intercalation and stripping to obtain a two-dimensional MXene nanosheet. Due to the unique two-dimensional large sheet structure of MXene nanosheets, as well as extraordinary conductivity and good structural strength, low lithium ion diffusion energy barrier (0.07eV) and excellent hydrophilicity, it has great prospects in lithium ion energy storage applications. However, MXene nanosheets are easily oxidized and have a low theoretical specific capacity (320mAh·g -1); at the same time, the layers have a greater tendency to self-stacking, which will hinder the transmission of lithium ions and lose active sites, which greatly limits its further application. In the face of these problems, inserting electrochemically active substances into the layers of MXene nanosheets is considered to be an effective method. For example, Lin et al. prepared MXene / CNF as a negative electrode material for lithium-ion batteries, inhibiting the self-stacking of MXene sheets. Experiments showed that the cycle stability of MXene / CNF was significantly improved (Lin, Z., Sun, D., Huang, Q., Yang, J., Barsoum, MW, & Yan, X. Carbon nanofiber bridged two-dimensional titanium carbide as a superior anode for lithium-ion batteries. J. Mater. Chem. A. 2015, 3, 14096-14100), but the study could not significantly improve the specific capacity of the electrode.

[0004] Tin dioxide is a transition metal oxide negative electrode material, which has attracted widespread attention due to its high specific capacity, low lithium insertion potential and abundant reserves. However, its shortcomings limit its further application, such as the volume expansion of up to 300% during charging and discharging, the resulting shedding and pulverization problems, and its poor conductivity. These problems make the specific capacity of the tin dioxide electrode decay rapidly, especially the rate performance at higher currents, and the cycle stability are poor, which cannot be used as an ideal negative electrode material for lithium ion capacitors. However, the mechanical strength and two-dimensional properties of MXene can alleviate the volume expansion of tin dioxide and improve the overall conductivity of the material. Therefore, it is an important strategy to prepare a good negative electrode material by combining tin dioxide with MXene. The patent "Granular Tin Dioxide / Two-Dimensional Nano-Titanium Carbide Composite Material and Application" shows that the multilayer organ-shaped MXene obtained by hydrofluoric acid etching and tin chloride pentahydrate are used as raw materials, and the SnO2 / MXene composite material loaded with tin dioxide can be obtained by hydrothermal reaction, and its specific capacity is greatly improved. However, MXene can be easily oxidized into titanium dioxide under hydrothermal conditions, resulting in structural destruction, which greatly damages its conductivity and structural strength, making it difficult to achieve good electrochemical performance. Moreover, the rate performance of the SnO2 / MXene negative electrode and the capacity retention rate under long cycles still need to be improved, which limits its practical application. In addition, the patent "A preparation method and application of a tin dioxide quantum dot / two-dimensional nano-titanium carbide composite material rich in oxygen vacancies" also prepares a quantum dot-type SnO2 / MXene composite material through a solvothermal reaction, and uses it for the negative electrode of a lithium ion capacitor, achieving enhanced specific capacity and cycle stability. However, the reaction conditions of high pressure, high temperature, and the presence of water and oxygen in the solvothermal reaction are obviously not conducive to the maintenance of the MXene structure and the original excellent performance. In this process, MXene is also easily oxidized and decomposed. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the primary purpose of the present invention is to provide an electrostatic self-assembled SnO2@NDPC / MXene nanocomposite material and a preparation method thereof. The method avoids the high-temperature water-containing oxygen-containing synthesis conditions that easily cause MXene oxidation, and synthesizes the SnO2@NDPC / MXene nanocomposite material through simple and controllable electrostatic self-assembly, which has the characteristics of high specific capacity, excellent rate performance, and good cycle stability.

[0006] Another object of the present invention is to provide the application of the above-mentioned electrostatically self-assembled SnO2@NDPC / MXene composite material as a negative electrode material for lithium-ion batteries LIBs and lithium-ion capacitors LICs, which has a good application prospect.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] An electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material with a special composition and structure. The nanocomposite material is a multi-level pore structure of nitrogen-doped porous carbon NDPC filled with nano SnO2 tightly wrapped by MXene nanosheets with a lateral size of 0.5μm to 2μm. Among them, the specific surface area of ​​NDPC is 1777~2137m 2 / g, total pore volume is 1.40~1.58m 3 / g, and the main pore diameter is mainly distributed in 2-5nm; the content of SnO2 is 31-53wt%, and the particle size is 4-6nm.

[0009] A method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material, specifically comprising the following steps:

[0010] (1) Ti3AlC2 ceramic powder was chemically etched in an acidic solution using lithium fluoride, and then ultrasonically exfoliated using deionized water as a solvent to obtain a single-layer MXene aqueous dispersion;

[0011] (2) urea, anhydrous zinc chloride and potassium chloride are mixed to form a deep eutectic solvent, coconut shell is added as a carbon source to the deep eutectic solvent, and then calcined to obtain NDPC material;

[0012] (3) dispersing the NDPC material obtained in step (2) with acetone, adding SnCl2 aqueous solution, magnetically stirring until the solvent evaporates naturally, vacuum drying and calcining to obtain nano-SnO2-filled nitrogen-doped porous carbon SnO2@NDPC powder;

[0013] (4) Ultrasonic mixing the monolayer MXene aqueous dispersion obtained in step (1) and the SnO2@NDPC powder obtained in step (3) in an aqueous solution, followed by electrostatic self-assembly, then discarding the supernatant and freeze-drying the obtained solid, and finally obtaining the SnO2@NDPC / MXene nanocomposite material.

[0014] Furthermore, the chemical etching method of step (1) is specifically performed according to the following steps: 3.2 g of lithium fluoride is added to 30-50 mL of 36 wt % hydrochloric acid and magnetically stirred to form an etching solution, and then 2 g of Ti3AlC2 ceramic powder is added and magnetically stirred at room temperature for 24 h to 72 h for etching; the etching product is collected and repeatedly washed by centrifugation with deionized water until the pH is between 5 and 6; the solid after centrifugal washing is re-dispersed with 100-200 mL of deionized water, and ultrasonically stripped in an ice-water bath under argon for 1 to 3 h, and the upper dark black solution is collected to obtain a single-layer MXene aqueous dispersion with a concentration of 0.5 mg / mL to 2 mg / mL.

[0015] Preferably, the Ti3AlC2 ceramic powder in step (1) has a purity of 99.9% and a particle size of 300 to 500 meshes, more preferably 400 meshes.

[0016] Preferably, the stirring time in step (1) is 48 h; the amount of deionized water used during redispersion is 150 mL; the ice-water bath ultrasonic stripping time under argon protection is 2 h; and the concentration of the collected single-layer MXene aqueous dispersion is about 1 mg / mL.

[0017] Furthermore, in step (2), the mass ratio of urea, anhydrous zinc chloride, potassium chloride and coconut shell is 4:6:1:1 to 4:6:1:3.

[0018] Preferably, the mass ratio of urea, anhydrous zinc chloride, potassium chloride and coconut shell in step (2) is 4:6:1:2.

[0019] Furthermore, the calcination temperature in step (2) is 700-900° C., the calcination atmosphere is nitrogen / argon, and the calcination time is 1-3 hours.

[0020] Preferably, the calcination temperature in step (2) is 800° C., the calcination atmosphere is nitrogen, and the calcination time is 2 h.

[0021] Furthermore, in step (3), the mass volume ratio of NDPC material to acetone is 0.25 g / mL to 1 g / mL; when preparing the SnCl2 aqueous solution, the concentration of SnCl2 is 1.0 g / mL; when preparing SnO2@NDPC, the amount of SnCl2 aqueous solution added is 400 to 1200 μL.

[0022] Preferably, in step (3), the mass volume ratio of NDPC material to acetone is 0.5 g / mL, and the amount of SnCl2 aqueous solution added is 800 μL.

[0023] Furthermore, the vacuum drying temperature in step (3) is 70 to 90° C., and the vacuum drying time is 8 to 12 hours.

[0024] Preferably, the vacuum drying temperature in step (3) is 80° C., and the vacuum drying time is 10 h.

[0025] Furthermore, the calcination temperature in step (3) is 260-300° C., the calcination atmosphere is nitrogen, the heating rate is 0.5-2° C. / min, and the calcination time is 1-3 h.

[0026] Preferably, the calcination temperature in step (3) is 280° C., the calcination atmosphere is nitrogen, the heating rate is 1° C. / min, and the calcination time is 2 h.

[0027] Furthermore, in step (4), the mass ratio of the monolayer MXene aqueous dispersion to the SnO2@NDPC powder is 1:10 to 4:10.

[0028] Preferably, in step (4), the mass ratio of the monolayer MXene aqueous dispersion to the SnO2@NDPC powder is 2:10.

[0029] Furthermore, in step (4), the ultrasonic time is 10 to 30 minutes; and the self-assembly time is 5 to 15 minutes.

[0030] Preferably, the ultrasonic time in step (4) is 20 min; and the self-assembly time is 10 min.

[0031] Furthermore, the freeze-drying temperature of step (4) is -30 to -50°C, and the freeze-drying time is 12h to 36h.

[0032] Preferably, the freeze-drying temperature in step (4) is -40°C and the freeze-drying time is 24 hours.

[0033] The present invention also provides an application of an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material in lithium ion batteries (LIBs) and lithium ion capacitors (LICs).

[0034] The present invention has the following advantages and effects compared with the prior art:

[0035] (1) The present invention provides a unique electrostatic self-assembly method, which avoids the high-temperature water-containing and oxygen-containing synthesis conditions that easily cause MXene oxidation. Due to their opposite charges, the prepared SnO2@NDPC and MXene nanosheets can be spontaneously and uniformly assembled by mixing them in the liquid phase. The method is simple and easy to operate.

[0036] (2) In the preparation method provided by the present invention, SnO2 particles with a particle size of about 5 nm are uniformly filled in the hierarchical pore structure of nitrogen-doped porous carbon (NDPC) as a matrix. The large amount of SnO2 particles filled provides a large specific capacity for the composite material. At the same time, since they are confined in the carbon pores, their volume expansion during the charge and discharge process is also alleviated, thereby improving the cycle stability of the composite material.

[0037] (3) In the preparation method provided by the present invention, a structure in which a single layer of MXene nanosheets tightly wraps the SnO2@NDPC substrate is obtained. The well-structured MXene nanosheets can further alleviate the volume expansion of SnO2, improve the overall conductivity of the composite material, and accelerate the lithium ion migration rate, improve the reaction kinetics, and further improve the cycle stability and rate performance of the prepared composite material. On the other hand, the SnO2@NDPC substrate wrapped in MXene can well inhibit the restacking of MXene nanosheets, which is beneficial to the exposure of active sites on the MXene surface.

[0038] (4) The electrostatically self-assembled SnO2@NDPC / MXene nanocomposite prepared by the present invention was used as the negative electrode of a lithium-ion battery to assemble a half-cell. -1 Under the same conditions, the specific capacity was maintained at 465 mAh g after 500 cycles. -1 The capacity retention rate is 90.2%, which shows good cycle stability. -1 At high current density, it can still show 300mAh·g -1 The specific capacity of the capacitor is 6097W·kg. -1 At high power density, its energy density is still as high as 55.9Wh·kg -1 , showing great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the XRD pattern of the electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material obtained in Example 1 of the present invention.

[0040] Figure 2 This is a transmission electron microscopy image of the electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material obtained in Example 1 of the present invention.

[0041] Figure 3 This is a scanning electron microscope image of the MXene nanosheets prepared in Example 1 of the present invention.

[0042] Figure 4 This is the nitrogen adsorption-desorption curve of NDPC and SnO2@NDPC obtained in Example 1 of the present invention.

[0043] Figure 5 This is the zeta potential diagram of SnO2@NDPC and MXene nanosheets prepared in Example 1 of the present invention.

[0044] Figure 6This is a rate performance diagram of the electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material obtained in Example 1 of the present invention.

[0045] Figure 7 The electrostatic self-assembled SnO2@NDPC / MXene nanocomposite obtained in Example 1 of the present invention is -1 Long cycle performance diagram at different current densities.

[0046] Figure 8 This is a graph showing the relationship between energy density and power density of a lithium ion capacitor assembled from the electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material obtained in Example 1 of the present invention.

[0047] Fig. 9 The electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material obtained in Example 1 of the present invention is used to assemble a lithium ion capacitor at 2A·g -1 Long cycle performance diagram at different current densities.

[0048] Fig.10 The electrostatic self-assembled SnO2@NDPC / MXene nanocomposite obtained in Example 2 of the present invention is -1 Long cycle performance diagram at different current densities.

[0049] Fig.11 The electrostatic self-assembled SnO2@NDPC / MXene nanocomposite obtained in Example 3 of the present invention is -1 Long cycle performance diagram at different current densities.

[0050] Fig.12 The electrostatic self-assembled SnO2@NDPC / MXene nanocomposite obtained in Example 4 of the present invention is -1 Long cycle performance diagram at different current densities.

[0051] Fig.13 The electrostatic self-assembled SnO2@NDPC / MXene nanocomposite obtained in Example 5 of the present invention is -1 Long cycle performance diagram at different current densities. DETAILED DESCRIPTION

[0052] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0053] Example 1

[0054] This embodiment includes the following steps:

[0055] (1) 3.2 g of lithium fluoride was added to 40 mL of 36 wt% hydrochloric acid and magnetically stirred to form an etching solution, and then 2 g of Ti3AlC2 ceramic powder with a particle size of 400 mesh was added and magnetically stirred at room temperature for 48 h for etching; the etching product was collected and repeatedly washed by centrifugation with deionized water until the pH was between 5 and 6; the solid after centrifugal washing was re-dispersed with 150 mL of deionized water, and ultrasonically stripped in an ice water bath under argon gas for 2 h, and the upper dark black solution was collected to obtain a single-layer MXene aqueous dispersion with a concentration of about 1 mg / mL.

[0056] (2) 4 g of urea, 6 g of anhydrous zinc chloride and 1 g of potassium chloride were mixed to form a deep eutectic solvent, 2 g of coconut shell was added as a carbon source, and the mixture was calcined at 800 °C for 2 h in a nitrogen atmosphere to obtain nitrogen-doped porous carbon (NDPC).

[0057] (3) Disperse 1 g of the NDPC obtained in step (2) with 2 mL of acetone, add 800 μL of 1.0 g / mL SnCl2 aqueous solution, stir magnetically until the solvent evaporates naturally, dry in vacuo at 80 °C for 10 h, and calcine at 280 °C for 2 h in a nitrogen atmosphere at a heating rate of 1 °C / min to obtain nano-tin dioxide-filled nitrogen-doped porous carbon (SnO2@NDPC) powder.

[0058] (4) 10 mL of the 1 mg / mL monolayer MXene aqueous dispersion obtained in step (1) and 50 mg of the SnO2@NDPC powder obtained in step (3) were ultrasonically mixed in an aqueous solution for 20 min, followed by self-assembly for 10 min. The supernatant was discarded and the obtained solid was freeze-dried at -40 ° C for 24 h to obtain a SnO2@NDPC / MXene nanocomposite material.

[0059] The XRD pattern of the electrostatically self-assembled SnO2@NDPC / MXene nanocomposite prepared in Example 1 is as follows: Figure 1 The XRD spectrum of the composite material shows obvious diffraction peaks of SnO2 and MXene (Ti3C2), while no diffraction peak of titanium dioxide appears, indicating that MXene is successfully composited without being oxidized.

[0060] The transmission electron microscopy image of the electrostatically self-assembled SnO2@NDPC / MXene nanocomposite prepared in Example 1 is as follows: Figure 2 As shown in Figure 2, it can be seen that MXene nanosheets wrap around SnO2@NDPC particles, and the particle size of SnO2 is about 5nm.

[0061] Figure 3This is a scanning electron microscope image of the MXene nanosheet prepared in Example 1. It can be seen from the image that the ultra-thin single-layer MXene nanosheet has a lateral size of 0.5 μm to 2 μm.

[0062] Figure 4 The nitrogen adsorption-desorption curves of NDPC and SnO2@NDPC prepared in Example 1 are shown in Figure 1. The nitrogen adsorption-desorption curves of NDPC show the characteristics of micropores and mesopores. The specific surface area of ​​NDPC is 2137 m 2 / g, and the total pore volume is 1.58m 3 / g. The large specific surface area and pore volume as well as the multi-level pore structure provide good conditions for the filling of SnO2. The nitrogen adsorption-desorption curve of SnO2@NDPC shows a large reduction in specific surface area and total pore volume, which assists in proving the filling of SnO2.

[0063] The zeta potential diagrams of SnO2@NDPC and MXene nanosheets prepared in Example 1 are shown in Figure 5 As shown, it can be seen that SnO2@NDPC and MXene nanosheets have zeta potentials of +44mV and -62mV, respectively. Due to the electrostatic effect, MXene nanosheets can spontaneously wrap SnO2@NDPC in aqueous solution to achieve electrostatic self-assembly.

[0064] The electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material prepared in Example 1 was used as the working electrode, a metal lithium sheet was used as the counter electrode and the reference electrode, a 1 mol / L LiPF6 solution using ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 as the solvent was used as the electrolyte, and Celgard 2500 was used as the separator to assemble a CR2025 button battery for testing. Figure 6 The rate performance diagram of the composite material is shown in Figure 2. -1 At a current density of 865 mAh g -1 When the current density increases to 2A·g -1 When 496 mAh g -1 The specific capacity of the battery is 57.3%, and the capacity retention rate is 57.3%. -1 At high current density, it can still show 300mAh g -1 The specific capacity has excellent rate performance. Figure 7 The composite material is 2A·g -1 Long cycle performance diagram under current density. After 500 cycles, the material has a specific capacity of 465 mAh g -1 , the capacity retention rate is 90.2% and the Coulombic efficiency is 100%, indicating that the composite material has excellent cycle stability.

[0065] The electrostatic self-assembled SnO2@NDPC / MXene nanocomposite prepared in Example 1 was used as the negative electrode, nitrogen-rich activated carbon (preparation method refers to Carbon 2020, 161, 25-35) was used as the positive electrode, 1 mol / L LiPF6 solution with ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 was used as the electrolyte, Celgard 2500 was used as the diaphragm, and encapsulated in a CR2025 button battery to assemble into a lithium ion capacitor for testing. The energy density-power density relationship diagram of the lithium ion capacitor is shown in the figure below. Figure 8 As shown, at a power density of 61.2 W kg -1 Its energy density is as high as 135.3Wh·kg -1 ; At a higher power density of 6097W·kg -1 Its energy density is still as high as 55.9Wh·kg -1 . At 2A·g -1 The lithium ion capacitor was tested for cycle stability at a current density of Fig. 9 As shown, after 3000 cycles, the capacity retention rate is 96.7%, indicating that the device has excellent cycle stability.

[0066] Example 2

[0067] This embodiment includes the following steps:

[0068] (1) 3.2 g of lithium fluoride was added to 30 mL of 36 wt% hydrochloric acid and magnetically stirred to form an etching solution, and then 2 g of Ti3AlC2 ceramic powder with a particle size of 400 mesh was added and magnetically stirred for 24 h at room temperature for etching; the etching product was collected and repeatedly washed by centrifugation with deionized water until the pH was between 5 and 6; the solid after centrifugal washing was re-dispersed with 200 mL of deionized water, and ultrasonically stripped in an ice water bath under argon gas for 1 h, and the upper dark black solution was collected to obtain a single-layer MXene aqueous dispersion with a concentration of about 0.5 mg / mL.

[0069] (2) 4 g of urea, 6 g of anhydrous zinc chloride and 1 g of potassium chloride were mixed to form a deep eutectic solvent, 2 g of coconut shell was added as a carbon source, and the mixture was calcined at 700 °C for 3 h under an argon atmosphere to obtain nitrogen-doped porous carbon (NDPC).

[0070] (3) Disperse 1 g of the NDPC obtained in step (2) with 1 mL of acetone, add 400 μL of a 1.0 g / mL SnCl2 aqueous solution, stir magnetically until the solvent evaporates naturally, dry in vacuo at 70 °C for 12 h, and calcine at 280 °C under a nitrogen atmosphere at a heating rate of 1 °C / min for 1 h to obtain nano-tin dioxide-filled nitrogen-doped porous carbon (SnO2@NDPC) powder.

[0071] (4) 20 mL of the 0.5 mg / mL single-layer MXene aqueous dispersion obtained in step (1) and 50 mg of the SnO2@NDPC powder obtained in step (3) were ultrasonically mixed in an aqueous solution for 30 min, followed by self-assembly for 5 min, the supernatant was poured off and the obtained solid was freeze-dried at -50°C for 12 h to obtain a SnO2@NDPC / MXene nanocomposite material.

[0072] The electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material prepared in Example 2 was used as the working electrode, a metal lithium sheet was used as the counter electrode and the reference electrode, a 1 mol / L LiPF6 solution using ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 as the solvent was used as the electrolyte, and a CR2025 button cell was assembled using Celgard 2500 as the separator for testing. Fig.10 The composite material is 2A·g -1 Long cycle performance diagram under current density. After 500 cycles, the material has a specific capacity of 389 mAh g -1 The capacity retention rate is 93.0% and the coulombic efficiency is 99.4%.

[0073] Example 3

[0074] This embodiment includes the following steps:

[0075] (1) 3.2 g of lithium fluoride was added to 50 mL of 36 wt % hydrochloric acid and magnetically stirred to form an etching solution, and then 2 g of Ti3AlC2 ceramic powder with a particle size of 300 mesh was added and magnetically stirred at room temperature for 48 h for etching; the etching product was collected and repeatedly washed by centrifugation with deionized water until the pH was between 5 and 6; the solid after centrifugal washing was re-dispersed with 150 mL of deionized water, and ultrasonically stripped in an ice water bath under argon gas for 3 h, and the upper dark black solution was collected to obtain a single-layer MXene aqueous dispersion with a concentration of about 1 mg / mL.

[0076] (2) 4 g of urea, 6 g of anhydrous zinc chloride and 1 g of potassium chloride were mixed to form a deep eutectic solvent, 3 g of coconut shell was added as a carbon source, and the mixture was calcined at 900 °C for 1 h in a nitrogen atmosphere to obtain nitrogen-doped porous carbon (NDPC).

[0077] (3) Disperse 1 g of the NDPC obtained in step (2) with 4 mL of acetone, add 1200 μL of a 1.0 g / mL SnCl2 aqueous solution, stir magnetically until the solvent evaporates naturally, dry in vacuum at 90 °C for 8 h, and calcine at 260 °C for 3 h at a heating rate of 0.5 °C / min in a nitrogen atmosphere to obtain nano-tin dioxide-filled nitrogen-doped porous carbon (SnO2@NDPC) powder.

[0078] (4) 5 mL of the 1 mg / mL monolayer MXene aqueous dispersion obtained in step (1) and 50 mg of the SnO2@NDPC powder obtained in step (3) were ultrasonically mixed in an aqueous solution for 10 min, followed by self-assembly for 15 min. The supernatant was discarded and the obtained solid was freeze-dried at -30°C for 36 h to obtain a SnO2@NDPC / MXene nanocomposite material.

[0079] The electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material prepared in Example 3 was used as the working electrode, a metal lithium sheet was used as the counter electrode and the reference electrode, a 1 mol / L LiPF6 solution using ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 as the solvent was used as the electrolyte, and a CR2025 button battery was assembled using Celgard 2500 as the separator for testing. Fig.11 The composite material is 2A·g -1 Long cycle performance diagram under current density. After 500 cycles, the specific capacity of the material is 391 mAh g -1 The capacity retention rate is 82.1% and the coulombic efficiency is 99.6%.

[0080] Example 4

[0081] This embodiment includes the following steps:

[0082] (1) 3.2 g of lithium fluoride was added to 40 mL of 36 wt% hydrochloric acid and magnetically stirred to form an etching solution, and then 2 g of Ti3AlC2 ceramic powder with a particle size of 500 mesh was added and magnetically stirred at room temperature for 48 h for etching; the etching product was collected and repeatedly washed by centrifugation with deionized water until the pH was between 5 and 6; the solid after centrifugal washing was re-dispersed with 150 mL of deionized water, and ultrasonically stripped in an ice water bath under argon gas for 1 h, and the upper dark black solution was collected to obtain a single-layer MXene aqueous dispersion with a concentration of about 1 mg / mL.

[0083] (2) 4 g of urea, 6 g of anhydrous zinc chloride and 1 g of potassium chloride were mixed to form a deep eutectic solvent, 2 g of coconut shell was added as a carbon source, and the mixture was calcined at 800 °C for 2 h in a nitrogen atmosphere to obtain nitrogen-doped porous carbon (NDPC).

[0084] (3) Disperse 1 g of the NDPC obtained in step (2) with 4 mL of acetone, add 800 μL of 1.0 g / mL SnCl2 aqueous solution, stir magnetically until the solvent evaporates naturally, dry in vacuum at 80 °C for 12 h, and calcine at 280 °C for 2 h at a heating rate of 1 °C / min in a nitrogen atmosphere to obtain nano-tin dioxide-filled nitrogen-doped porous carbon (SnO2@NDPC) powder.

[0085] (4) 20 mL of the 1 mg / mL monolayer MXene aqueous dispersion obtained in step (1) and 50 mg of the SnO2@NDPC powder obtained in step (3) were ultrasonically mixed in an aqueous solution for 30 min, followed by self-assembly for 5 min. The supernatant was poured off and the obtained solid was freeze-dried at -50°C for 24 h to obtain a SnO2@NDPC / MXene nanocomposite material.

[0086] The electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material prepared in Example 4 was used as the working electrode, a metal lithium sheet was used as the counter electrode and the reference electrode, a 1 mol / L LiPF6 solution using ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 as the solvent was used as the electrolyte, and Celgard 2500 was used as the separator to assemble a CR2025 button battery for testing. Fig.12 The composite material is 2A·g -1 Long cycle performance diagram under current density. After 500 cycles, the material has a specific capacity of 406 mAh g -1 The capacity retention rate is 90.6% and the coulombic efficiency is 99.5%.

[0087] Example 5

[0088] This embodiment includes the following steps:

[0089] (1) 3.2 g of lithium fluoride was added to 40 mL of 36 wt% hydrochloric acid and magnetically stirred to form an etching solution, and then 2 g of Ti3AlC2 ceramic powder with a particle size of 400 mesh was added and magnetically stirred at room temperature for 48 h for etching; the etching product was collected and repeatedly washed by centrifugation with deionized water until the pH was between 5 and 6; the solid after centrifugal washing was re-dispersed with 150 mL of deionized water, and ultrasonically stripped in an ice water bath under argon gas for 2 h, and the upper dark black solution was collected to obtain a single-layer MXene aqueous dispersion with a concentration of about 1 mg / mL.

[0090] (2) 4 g of urea, 6 g of anhydrous zinc chloride and 1 g of potassium chloride were mixed to form a deep eutectic solvent, 1 g of coconut shell was added as a carbon source, and the mixture was calcined at 700 °C for 2 h in a nitrogen atmosphere to obtain nitrogen-doped porous carbon (NDPC).

[0091] (3) Disperse 1 g of the NDPC obtained in step (2) with 2 mL of acetone, add 400 μL of a 1.0 g / mL SnCl2 aqueous solution, stir magnetically until the solvent evaporates naturally, dry in vacuo at 80 °C for 12 h, and calcine at 300 °C for 1 h in a nitrogen atmosphere at a heating rate of 2 °C / min to obtain nano-tin dioxide-filled nitrogen-doped porous carbon (SnO2@NDPC) powder.

[0092] (4) 20 mL of the 1 mg / mL monolayer MXene aqueous dispersion obtained in step (1) and 50 mg of the SnO2@NDPC powder obtained in step (3) were ultrasonically mixed in an aqueous solution for 10 min, followed by self-assembly for 10 min. The supernatant was discarded and the obtained solid was freeze-dried at -40 ° C for 24 h to obtain a SnO2@NDPC / MXene nanocomposite material.

[0093] The electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material prepared in Example 5 was used as the working electrode, a metal lithium sheet was used as the counter electrode and the reference electrode, a 1 mol / L LiPF6 solution using ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 as the solvent was used as the electrolyte, and Celgard 2500 was used as the separator to assemble a CR2025 button battery for testing. Fig.13 The composite material is 2A·g -1 Long cycle performance diagram under current density. After 500 cycles, the material has a specific capacity of 330 mAh g -1 The capacity retention rate is 88.7% and the coulombic efficiency is 99.7%.

[0094] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material, characterized in that: The following steps are involved: (1) Ti3AlC2 ceramic powder is chemically etched in an acidic solution using lithium fluoride, and then ultrasonically exfoliated using deionized water as a solvent to obtain a single-layer MXene aqueous dispersion; the concentration of the single-layer MXene aqueous dispersion is 0.5-2 mg / mL; (2) Urea, anhydrous zinc chloride and potassium chloride are mixed to form a deep eutectic solvent, coconut shell is added as a carbon source to the deep eutectic solvent, and then calcined to obtain NDPC material; (3) dispersing the NDPC material obtained in step (2) with acetone, adding SnCl2 aqueous solution, magnetically stirring until the solvent evaporates naturally, vacuum drying and calcining to obtain nano-SnO2-filled nitrogen-doped porous carbon SnO2@NDPC powder; (4) The monolayer MXene aqueous dispersion obtained in step (1) and the SnO2@NDPC powder obtained in step (3) are ultrasonically mixed in an aqueous solution, followed by electrostatic self-assembly, and then the supernatant is discarded and the obtained solid is freeze-dried to finally obtain the SnO2@NDPC / MXene nanocomposite material.

2. The method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1, characterized in that: The mass ratio of urea, anhydrous zinc chloride, potassium chloride and coconut shell in step (2) is 4:6:1:1 to 4:6:1:

3.

3. The method for preparing an electrostatic self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1, characterized in that: The calcination temperature in step (2) is 700-900° C., the calcination atmosphere is nitrogen or argon, and the calcination time is 1-3 hours.

4. The method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1, characterized in that: In step (3), the mass volume ratio of NDPC material to acetone is 0.25 g / mL~1.00 g / mL; the amount of SnCl2 aqueous solution added is 400~1200 μL.

5. The method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1, characterized in that: The temperature of the vacuum drying in step (3) is 70-90°C, and the time of the vacuum drying is 8-12 hours. The temperature of the calcination in step (3) is 260-300°C, the calcination atmosphere is nitrogen, the heating rate is 0.5-2°C / min, and the calcination time is 1-3 hours.

6. The method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1, characterized in that: In step (4), the mass ratio of the monolayer MXene aqueous dispersion to the SnO2@NDPC powder is 1:10 to 4:

10.

7. The method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1, characterized in that: The ultrasonic time in step (4) is 10 to 30 minutes; the self-assembly time in step (4) is 5 to 15 minutes.

8. The method for preparing an electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1, characterized in that: The freeze-drying temperature in step (4) is -30 to -50°C, and the freeze-drying time is 12h to 36h.

9. An electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material prepared by the preparation method of claim 1, characterized in that: The nanocomposite material is a hierarchical pore structure of nitrogen-doped porous carbon NDPC filled with nano-SnO2, in which MXene nanosheets with a lateral size of 0.5 to 2 μm are tightly wrapped; the content of SnO2 is 31 to 53 wt%, and the particle size is 4 to 6 nm; the specific surface area of ​​NDPC is 1777 to 2137 m 2 / g, and the total pore volume is 1.40~1.58 m 3 / g, and the main pore size is distributed in the range of 2~5 nm.

10. Application of the electrostatically self-assembled SnO2@NDPC / MXene nanocomposite material according to claim 1 in lithium ion batteries and lithium ion capacitors.

Citation Information

Patent Citations

  • SnO2-modified N, P-codoped porous carbon supercapacitor material

    CN112599363A

  • Three-dimensional structure MXene / SnO2 / C negative electrode composite material and preparation method thereof

    CN114039051A